Simple and convenient preparation of novel 6,8-disubstituted quinoline derivatives and their promising anticancer activities - Okten, Salih; Cakmak, Osman; Erenler, Ramazan; Yuce, Onem; Tekin, Saban (Tubitak Scientific & Technological Research Council Turkey, 2013)
A short and easy route is described for 6,8-disubstituted derivatives of quinoline and 1,2,3,4-tetrahydroquinoline from 6,8-dibromoquinolines 2 and 7 by various substitution reactions. While copper-promoted substitution of 6,8-dibromide 2 produced monomethoxides 3 and 4, a prolonged reaction time mainly afforded dimethoxide 6 instead of 5, whose aromatization with DDQ and substitution reaction of dibromide 7 with NaOMe in the presence of CuI also gave rise to dimethoxide 6. Several 6,8-disubstituted quinolines were obtained by treatment of 6,8-dibromoquinoline (7) with n-BuLi followed by trapping with an electrophile [Si(Me)(3)Cl, S-2(Me)(2), and DMF]. Furthermore, 7 was also converted to mono and dicyano derivatives. The anticancer activities of compounds 2, 7, 6, 12, 13, 15, and 16 against HeLa, HT29, and C6 tumor cell lines were tested, and 6,8-dibromo-1,2,3,4-tetrahydroquinoline (2) and 6,8-dimethoxyquinoline (6) showed significant anticancer activities against the tumor cell lines.
Keywords: Anticancer effect; bromoquinoline; cyanoquinoline; lithium-bromine exchange; methoxyquinoline; quinoline derivatives; SUBSTITUTED QUINOLINES; Chemistry; Engineering